Patients' Views With Regard to Personal Recovery in Forensic Psychiatry in German-Speaking Switzerland—An Explorative Study - Schoppmann, Susanne; Balensiefen, Joachim; Lau, Steffen; Graf, Marc; Hachtel, Henning (Frontiers in Psychiatry, 2021)
Recovery orientation (RO) is a modality of supporting patients to improve self-determination, leading a meaningful life and well-being in general. This approach is widely studied in general psychiatry but evidence is lacking for forensic inpatient settings in German speaking Switzerland. While secure forensic clinics tend to be regarded as total institutions, which are anathema to RO, a project to implement RO interventions in this setting was financed by the Swiss Federal Office of Justice. This explorative study investigates baseline expectations and views of patients in forensic wards in German-speaking Switzerland in the context of a recovery-oriented intervention. Six focus groups with 37 forensic inpatients were conducted. Thematic analysis revealed two major and several subthemes. The major theme ‘heteronomy’ includes the subthemes ‘stigmatization and shame’, ‘coercion’, ‘lack of support’, ‘mistrust’, ‘waiting’ and ‘structural impediments’. The subthemes ‘learning to live with the disorder and working on oneself’, ‘participation’, ‘connectedness’, ‘confidence’ and ‘joie de vivre’ belong to the major theme ‘regaining self-determination’. In this way results of prior research are extended to forensic peculiarities and possible future investigations could be informed of probable baseline findings. Furthermore, the personal views of patients are discussed in detail regarding their possible influence on therapeutic outcomes and personal recovery. These findings should be of help to therapeutic staff in the respective setting to be better informed about and to counter the effects of heteronomy and long-term hospitalization. Important in this regard is the concept of procedural justice and the subjective client’s perception thereof.